Manmath Pooja - Hawaldar, Asmita (Integrated Journal for Research in Arts and Humanities, 2023)
Lepakshi is a small town1 situated in Hindupur taluka of Anantpur district, Andhra Pradesh. Veerbhadra temple located in Lepakshi is famous for monumental temple architecture of Vijaynagar Empire period. The extensive mural paintings executed on the walls and temple ceilings are world famous. One of the painting ‘Girija Kalyanam’ depicts story of marriage of Shiv and Parvati. It is a narrative panel. It starts with the painting famously known as ‘Parvati’s toilet’. In this paper, I have tried to prove that it is not ‘Parvati’s toilet’ but ‘Manmath Pooja’.